2001
DOI: 10.1002/rcm.510
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of reduction of Cu(II) complexes in positive‐ion mode electrospray mass spectrometry

Abstract: The electrospray ionization mass spectrometry (ESI-MS) behavior of seven Cu(II) complexes with tetradentate ligands has been studied. An unexpected reduction process, in positive ion mode, of the Cu oxidation state was observed, and shown to be due to charge transfer between the metal complex and the solvent molecules in the gas phase. Ion trap collision-induced dissociation experiments and deuterated solvents were used to support the proposed mechanism that is not a common electrochemical redox reaction at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 11 publications
4
78
0
1
Order By: Relevance
“…The 2BCP-Cu + absorbance was higher than the Cu + complex formed following the dissolution of a copper(II) salt (dot line) in the spray medium. This small quantity of the 2:1 complex in solution after 30 min could come from reduction of Cu 2+ complexes by methanol, where the reaction has a small kinetic constant, similar to those observed by Gianelli et al [26].…”
Section: Bathocuproine Complexessupporting
confidence: 81%
See 1 more Smart Citation
“…The 2BCP-Cu + absorbance was higher than the Cu + complex formed following the dissolution of a copper(II) salt (dot line) in the spray medium. This small quantity of the 2:1 complex in solution after 30 min could come from reduction of Cu 2+ complexes by methanol, where the reaction has a small kinetic constant, similar to those observed by Gianelli et al [26].…”
Section: Bathocuproine Complexessupporting
confidence: 81%
“…Schrö der et al have also observed this phenomenon by increasing the cone voltage tension [25]. Gianelli et al have reported the effect of the presence of solvents on Cu 2+ reduction and correlated the production of Cu + with the ionization energy of alcohols [26]. Cu + ions formed in the gas-phase can react with ligands offering a better affinity for Cu + .…”
Section: Discussionmentioning
confidence: 93%
“…solvent or analyte. [41][42][43][44] So, the presence of Cu + when using a copper electrode can be explained by two processes. 37 First, electrogenerated copper(II) ions can be reduced in solution or in the gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the experiment, these data clearly show that the mono-copper complexes are constituted by 76% Ϯ 3% of Cu 2ϩ under these experimental conditions. This can be due either to the binding of copper ions on different sites, (RVYIH(Cu 2ϩ )PF or R(Cu ϩ )VYIHPF), or to a mixed population of Cu 2ϩ / Cu ϩ on a given site, (e.g., RVYIH(Cu 2ϩ/ϩ )PF), induced by an in situ reduction of Cu 2ϩ -histidine complexes in the gas phase [20,[22][23][24]35]. As the copper electrode is able to produce either Cu 2ϩ or Cu ϩ aqueous ions, Cu 2ϩ -histidine and/or Cu ϩ -arginine complexes can in principle be concomitantly formed.…”
Section: Copper-angiotensin III Complexesmentioning
confidence: 99%